Corrispondenze - Bortolotto, Mario 1927-2017 (Milan Adelphi, 2010)
A Mozart far less Apollonian than he is usually portrayed, a tragic and modern Mendelssohn and an elderly Verdi, saturated with vitality and contradictions; a letter to the 'knight Gluck', the interview that Brahms decided to give exclusively to posterity and Hindemith and Strawinsky's fierce criticism of the 'frightening giant' Beethoven: these are just some of the surprises that Mario Bortolotto's new musical breviary has in store for us. From Schubert to Mahler, from Rossini to Wagner, Tchaikovsky and Debussy, none of the great masters are missing from the roll-call, and yet there is also room for lesser explored authors and themes: Cherubini, Auber, Schmidt, the operetta and Alpine choirs already dear to Benedetti Michelangeli, an unpublished Leopardi musical theorist and Berlioz's colourful epistolary... But Bortolotto's favourite environment is undoubtedly the theatre, so that on several occasions we see him probing, with loving and at the same time severe solicitude, the state of health of the opera - 'this artefact that holds a little of the waffling and a little of the magical'. Peregrinating from the unreachable Viennese Staatsoper to the Parisian stages and from St. Petersburg to the Colón in Buenos Aires, to those 'demanding little theatres' that alone, in Italy, resist the desolating 'reduction of the so-called repertoire', Bortolotto examines singers and conductors, pierces here and there the 'unfortunate gimmicks' and the 'massive ignorance' of certain directors, yet is always ready to be enchanted by the miracle of a perfect performance. Escorted through a labyrinth of artistic, literary and musical events by a nonchalant but suspiciously omniscient guide, we understand, in short, how the music that we inexplicably insist on calling classical, far from being the superfluous 'soundtrack' of western cultural life, is an inalienable and fundamental part of it. (Translated with DeepL.com)
Includes index.
Keywords: Music history; Music criticism; Theater history